No Pain, No Gain? Household Beliefs and Stock Market Participation - Ming Gao (Economics Letters, 2019)
This paper investigates whether household beliefs on the determinants of success affect their stock market participation decisions. Using national survey data from China, I show that Chinese households believe that personal effort is the most influential factor in people’s success, followed by family social connections, aptitude, and luck. Moreover, households that believe more in effort are less likely to participate in the stock market, while those who place more emphasis on family social connections are more likely to participate. The negative (positive) effects of effort (family social connections) are more profound for agricultural (workplace-affiliated) households. Further, I offer belief mechanisms to explain the heterogeneity of stock market participation for different occupations.